Development of Soft Skills of higher education students in distance learning - Oliinyk , N. (Problems of Engineer-Pedagogical Education, 2023)
The article discusses the development of soft skills of students in the context of using distance learning technologies. Drawing upon an in-depth examination of scholarly literature, the Higher Education Standard of Ukraine for the first (bachelor's) level of higher education within the domain of knowledge categorized as "Service Sector," with a specific focus on specialty 241, titled "Hotel and Restaurant Business," in conjunction with insights gleaned from the surveys of students and employers, a comprehensive list of soft skills has been identified. These identified soft skills hold pronounced significance for the day-to-day vocational endeavors of professionals within the realm of the hospitality industry. Empirical findings underscore that the effectiveness of developing flexible skills in an online environment depends on a combination of factors such as teaching methods, teacher competence, student self-discipline level, and the availability of technical infrastructure. The paper proposes a model of a virtual educational environment that is a comprehensive system that includes video lessons, webinars, tasks, games and simulations, forums for discussion and collaboration, assessment, and tracking of student progress, and identifies conditions for its effective functioning. Such a virtual learning environment can be an effective tool for developing students’ soft skills under the following conditions: the availability of necessary technical means and software, the availability of a qualified teacher who ensures effective communication and organization of the learning process, the availability of quality and understandable learning materials, which include video lessons, text materials, tasks and testing, ensuring the possibility of interaction between course participants, including discussion of materials, joint solution of tasks and projects, creating the possibility of independent work of course participants, providing access to educational materials at any time, and the possibility of working at their own pace, ensuring the possibility of feedback and assessment of acquired knowledge and skills, as well as ensuring the possibility of further self-development and improvement of their skills. The developed model was implemented using the Moodle LMS environment. The model is based on the idea of dividing the virtual class into different zones (self-study zone, communication zone, creativity zone, assessment zone), which allows students to develop various Soft Skills. Each zone has its own purpose and content. For each zone, appropriate activities and resources from the Moodle LMS are selected. As a promising direction for research, the author proposes the use of neural networks for the formation of Soft Skills. Neural networks can be a useful tool for developing Soft Skills, considering their ability to perform various tasks related to increasing productivity, improving communication, and fostering creativity.